Academic Leadership: Creating Successful (New) Leaders & Preserving Institutional Memory - Robert Williams; Rosemary Fithian Guruswamy; Dan Woods (Academic Chairpersons Conference Proceedings, 2017)
Participants will consider the following topics: identifying & articulating the primary responsibilities of a leadership position; preserving important institutional mores and memories during a change in leadership; developing institutional structures and materials to support new leaders in such transitions. Participants will leave with an action plan/checklist for supporting new leaders.
Keywords: Leadership Transitions; Institutional Culture; Institutional Memory; Continuity of Leadership; Successful Leadership Strategies; Leadership Transparency